2011
DOI: 10.1007/s00392-011-0372-6
|View full text |Cite
|
Sign up to set email alerts
|

Platelet inhibition and GP IIb/IIIa receptor occupancy by intracoronary versus intravenous bolus administration of abciximab in patients with ST-elevation myocardial infarction

Abstract: Acutely, direct intracoronary bolus injection resulted in a more pronounced local inhibition of platelet function and a higher degree of GP IIb/IIIa receptor occupancy as compared to standard intravenous bolus injection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 24 publications
0
17
0
1
Order By: Relevance
“…On the other hand, during primary PCI, the intracoronary administration of abciximab can be easily performed using a guiding catheter, which may result in a more pronounced local inhibition of platelet function and a higher degree of GP IIb/IIIa receptor occupancy when compared to standard intravenous bolus injection 65. Single cases of dethrombotic effect using an intracoronary bolus have been reported 6668.…”
Section: Other Abciximab Administration Strategiesmentioning
confidence: 99%
“…On the other hand, during primary PCI, the intracoronary administration of abciximab can be easily performed using a guiding catheter, which may result in a more pronounced local inhibition of platelet function and a higher degree of GP IIb/IIIa receptor occupancy when compared to standard intravenous bolus injection 65. Single cases of dethrombotic effect using an intracoronary bolus have been reported 6668.…”
Section: Other Abciximab Administration Strategiesmentioning
confidence: 99%
“…With a rationale that more potent ADP receptor blockers, bivalirudin, thrombus aspiration, and primary stenting are available for most of the STEMI patients and that the continuous intravenous infusion might not be benefitial to further improve outcome but increase the risk of bleeding, Gu et al [23] applied intracoronary bolus of abciximab only with no maintenance infusion and found better blush grade and reduced infact size in those with intracoronary application of abciximab. The intracoronary application of abciximab results in lower platelet reactivity in coronary sinus blood samples when compared with intravenous dosing [24]. A randomized trial comparing these regimens with/without maintenance infusion in combination with modern mechanical reperfusion devices needs to be performed.…”
Section: Pharmacotherapymentioning
confidence: 99%
“…Recent studies showed a suboptimal platelet inhibition lasting the first 2 hours after prasugrel administration which might be obviated co-administering a bolus of GP inhibitors intravenously [58]. Therefore in the setting of STEMI patients the role of GP IIb/IIIa inhibitors is yet important, considering that intracoronary administration showed higher local receptor occupancy and improved microvascular perfusion [59-61]. …”
Section: Gp Versus Adp Inhibitorsmentioning
confidence: 99%